CITRAAN DALAM ANTOLOGI PUISI SURAT KOPI KARYA JOKO PINURBO - Dodi Bramfi Imanuel; Erlina Zahar; Firman Tara (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this research is to describe the imagery contained in the poetry anthology of Joko Pinurbo's Surat Kopi. This research is qualitative descriptive. The main data in this research is written data in the form of expressions containing imagery elements found in the poetry anthology of Surat Kopi by Joko Pinurbo. The data is collected by using library study techniques focused in analyzing the imagery found in the poetry anthology Surat Kopi by Joko Pinurbo. Meanwhile in analyzing the data, analysis and description techniques were used. From the results of the research, it can be concluded that there are imagery of vision, auditory in the 21 poems in the anthology of Surat Kopi by Joko Pinurbo. The description is as follows, (1) there is a vision imagery in the 21 poems of Surat Kopi by Joko Pinurbo, the 21 poems depict that what the poet sees as if it can also be seen by poetry readers, the imagery of visions found are 19 expressions. (2) there is an image of hearing in 21 poems of Surat Kopi by Joko Pinurbo, in the poem describes that the voice heard by the poet as if it can also be heard by the reader of poetry, the image of hearing found are 7 expressions. (3) there is an image of motion in the 21 poems of Surat Kopi by Joko Pinurbo, in the poem illustrates that the things felt moving by the poet as if also felt directly by the reader of poetry, the image of motion found are 11 expressions. Thus the total imagery found in the 21 poems of Surat Kopi by Joko Pinurbo are 37 expressions.